Mendorong transparansi desa: Kiprah PSM dalam penyusunan laporan keuangan BUMDesa yang andal - Siswanto Siswanto (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
This study examines the role of Community Self-Help Facilitators (Penggerak Swadaya Masyarakat/PSM) in improving the quality of financial reporting in Village-Owned Enterprises (BUMDes) in Sleman Regency, Indonesia. The research adopts a qualitative case study approach, involving observation and in-depth interviews with 34 active PSMs. Findings reveal that PSMs play a strategic role in assisting BUMDes in complying with financial reporting standards mandated by the Ministry of Villages Regulation No. 136/2022. Their support includes providing technical guidance, enhancing accountability, and promoting transparency in financial management. However, several challenges were identified, including limited accounting competence among PSMs, insufficient and irregular training, weak internal governance within BUMDes, and inadequate local government support. The study concludes that a holistic approach is needed to improve financial reporting quality, including continuous training programs for PSMs and BUMDes managers, formal integration of PSM roles into village governance systems, the use of digital tools for financial recording, and stronger multi-stakeholder support. Public interest statements BUMDes often struggle to prepare standardized financial reports due to limited accounting skills. This study highlights the vital role of Community Self-Help Facilitators (PSM) in providing guidance and capacity building to improve financial transparency, accountability, and sustainability in rural governance and economic development.